Multilocus Sequence Typing and Antimicrobial Resistance of Campylobacter jejuni Isolated from Dairy Calves in Austria - Klein-Jöbstl, Daniela; Sofka, Dmitri; Iwersen, Michael; Drillich, Marc; Hilbert, Friederike (Frontiers in Microbiology, 2016)
Human campylobacteriosis is primarily associated with poultry but also cattle. In this study, 55 Campylobacter jejuni strains isolated from 382 dairy calves’ feces were differentiated by multilocus sequence typing and tested for antimicrobial resistance. The most prevalent sequence type (ST) was ST883 (20.0%), followed by ST48 (14.5%), and ST50 (9.1%). In contrast to ST48 and ST50, ST883 has rarely been described in cattle previously. Furthermore, risk factor analysis was performed for the presence of the most prevalent STs in these calves. Multiple regression analysis revealed that the type of farm (organic versus conventional) and calf housing (place, and individual versus group) were identified as significantly (p<0.05) associated with the presence of ST883 in calves, and ST50 was associated with calf diarrhea. Antimicrobial resistance was detected in 58.2% of the isolates. Most of the resistant isolates (81.3%) were resistant to more than one antimicrobial. Most frequently, resistance to ciprofloxacin (49.1%), followed by nalidixic acid with (42.8%), and tetracycline (14.5%) was observed. The results of the present study support the hypothesis that dairy calves may serve as a potential reservoir for Campylobacter jejuni and pose a risk for transmission, including antimicrobial resistant isolates to the environment and to humans.